Gerakan Sweeping Kunjungan Rumah Ibu Hamil Di Wilayah Kerja Puskesmas Sungai Turak - Hartuti Hartuti; Meldawati Meldawati; Siti Noor Hasanah (Jurnal Pengabdian Ilmu Kesehatan, 2024)
A country's success in improving maternal health can be seen from the reduction in maternal and infant mortality rates. Empowering posyandu cadres and community leaders plays an important role in improving the health of pregnant women and reducing MMR. Based on an analysis of the situation in society, there are still pregnant women who do not have their pregnancies checked early at the Community Health Center or Posyandu. The proposed solution is to carry out sweeping home visits for pregnant women, who are recorded as not having made ANC visits to health services. The home visit method is carried out to provide education and facilitate access to services and information to families and/or relatives about pregnancy health. From the activity steps, it was found that there were 3 pregnant women who had not made a K2 return visit to the Puskesmas, and 1 pregnant mother who had not made a K3 visit. Sweeping visits to pregnant women's homes were carried out in January 2024. The visits were carried out by midwives, together with cadres, on 4 pregnant women.